PENGGUNAAN DESAIN FAÇADE GANDA KACA DI GEDUNG FAKULTAS PSIKOLOGI UNIVERSITAS DIPONEGORO BERDASARKAN PERATURAN PEMERINTAH - Kahayanto, Dian Wibowo; Dwiyanto, Agung; Setowati, Erni (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
Indonesia with its tropical climate should adopt green buildings arranged by the Government Regulation. The green buildings usually use the Double Skin Façade (DF) system to mitigate heat transfer into interior spaces. One of the green buildings at Diponegoro University is the Psychology Faculty. This research aims to analyze this green building based on Government Regulation, such as stipulated in SNI 6389-2011 and the Ministerial Regulation of PUPR of the Republic of Indonesia Number 21, dated 2021, which mandates that the overall heat transfer value of the outer building should not exceed 35 W/m². By applying the descriptive qualitative method, the Overall thermal Transfer Value (OTTV) was measured. The results show that Faculty of Psychology building at Diponegoro University utilizes the DSF system, with stopsol Asahimas dark blue glass as the outer skin and predominantly brick inner skin equipped with operable windows with the Overall Thermal Transfer Value (OTTV) value of 42.6 W/m². However, the comprehensive building OTTV value is 54.94 W/m², classified as non-compliant with green building design criteria based on the Government Regulations.